Factorise:5(2a+b)^2-(2a+b)-4

Asked by  | 15th Oct, 2012, 07:19: PM

Expert Answer:

Answer : Given : 5(2a + b)2 - (2a + b) - 4
To factorise the above equation.

=5(2a + b)2 - (2a + b) - 4

= 5(2a + b)2 - 5(2a + b) + 4(2a + b) - 4

= 5(2a + b) [(2a + b) - 1] + 4 [(2a + b) - 1]

= [5(2a + b) + 4] [(2a + b) - 1]

= (10a + 5b + 4) (2a + b - 1) Answer 

Answered by  | 15th Oct, 2012, 07:36: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.